The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1021/cb200178w
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-Mediated Cellular Uptake Mechanism That Couples to Intracellular Storage

Abstract: Cells are known to take up molecules through membrane transport mechanisms such as active transport, channels, and facilitated transport. We report here a new membrane transport mechanism that employs neither cellular energy like active transport nor a preexisting electrochemical gradient of the free substrate like channels or facilitated transport. Through this mechanism, cells take up vitamin A bound with high affinity to retinol binding protein (RBP) in the blood. This mechanism is mediated by the RBP recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
119
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(132 citation statements)
references
References 30 publications
5
119
0
1
Order By: Relevance
“…for trapping of glucose by ATP-dependent phosphorylation). Besides LRAT, CRBP1 was suggested as an intracellular ROL acceptor from in vitro studies (16). Interestingly, we found that Lrat Ϫ/Ϫ mice displayed relatively high levels of CRBP1 in tissues as compared with control mice used in this study.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…for trapping of glucose by ATP-dependent phosphorylation). Besides LRAT, CRBP1 was suggested as an intracellular ROL acceptor from in vitro studies (16). Interestingly, we found that Lrat Ϫ/Ϫ mice displayed relatively high levels of CRBP1 in tissues as compared with control mice used in this study.…”
Section: Discussionmentioning
confidence: 47%
“…In cell culture studies, CRBP1 has been implicated in STRA6-mediated vitamin A uptake (16). Interestingly, Lrat Ϫ/Ϫ mice showed elevated CRBP1 protein in the liver, lung, and adipose tissue as compared with wild type control animals (Fig.…”
Section: Rol Uptake From Holo-rbp In Vivo Depends On Lratmentioning
confidence: 94%
See 2 more Smart Citations
“…[22] STRA6, sadece retinol bağlayıcı proteini bağlamakla kalmaz aynı zamanda vitamin A-RBP kompleksinden vitamin A' nın ayrılmasını katalize eder. [22,23] Embryonik gelişimde ve erişkinde yaygın olarak eksprese edilen bu molekülün aynı zamanda koroid pleksus da dahil olmak üzere çeşitli beyin bölgelerinde ekpresyonu mevcuttur. [24] …”
Section: Antioksidan Vitaminler Vitamin Aunclassified